2012
DOI: 10.1080/00207160.2011.554540
|View full text |Cite
|
Sign up to set email alerts
|

Dengue disease, basic reproduction number and control

Abstract: Dengue is one of the major international public health concerns. Although progress is underway, developing a vaccine against the disease is challenging. Thus, the main approach to fight the disease is vector control. A model for the transmission of Dengue disease is presented. It consists of eight mutually exclusive compartments representing the human and vector dynamics. It also includes a control parameter (insecticide) in order to fight the mosquito. The model presents three possible equilibria: two disease… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 24 publications
2
50
0
5
Order By: Relevance
“…The intervention has not yet been used into the mathematical model [16]. In [19], the mathematical model with only insecticide campaign intervention is discussed. It has been shown that, with a steady insecticide campaign, it is possible to reduce the number of infected humans and mosquitoes and prevent an outbreak that could transform an epidemiological episode to an endemic disease [19].…”
Section: Journal Of Applied Mathematicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The intervention has not yet been used into the mathematical model [16]. In [19], the mathematical model with only insecticide campaign intervention is discussed. It has been shown that, with a steady insecticide campaign, it is possible to reduce the number of infected humans and mosquitoes and prevent an outbreak that could transform an epidemiological episode to an endemic disease [19].…”
Section: Journal Of Applied Mathematicsmentioning
confidence: 99%
“…In [19], the mathematical model with only insecticide campaign intervention is discussed. It has been shown that, with a steady insecticide campaign, it is possible to reduce the number of infected humans and mosquitoes and prevent an outbreak that could transform an epidemiological episode to an endemic disease [19]. A year after the research discussed in [19], it was updated [20], and the mathematical model for dengue was updated continuously with all controls included, that is, (1) proportion of larvicide, (2) proportion of adulticide, and (3) proportion of mechanical control.…”
Section: Journal Of Applied Mathematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the expected number of secondary cases produced in a complete susceptible population, by a typical infected individual during his/her entire period of infectiousness [15]. In the absence of controls (u 1 = u 2 ≡ 0), it is known (see [5]) that the basic reproduction number for system (1) is proportional to the transmission coefficient β:…”
mentioning
confidence: 99%
“…While the usefulness of optimal control theory in epidemiology is nowadays well recognized [2,9,10,11,14,15], results pertaining to tuberculosis are a rarity [7], and specific studies for the situation of Angola nonexistent. Our aim in this paper is thus to use real data from Angola to study optimal strategies for the minimization of the number of active TB infectious and persistent latent individuals, taking into account the cost of the measures for the treatment of these individuals.…”
mentioning
confidence: 99%